2016
DOI: 10.1002/pola.28077
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and flame retardant potential of polyols based on bisphenol‐S

Abstract: Polyether polyols based on bisphenol-S were prepared by alkoxylation and compared with analogs based on bisphenol-A, as well as standard aromatic polyester, and polyether polyols for viscosity and temperature stability. Thermooxidative stability was determined by thermo-gravimetric analysis, pyrolysis gas chromatography/mass spectroscopy, and evolved gas analysis mass spectroscopy. Incorporation of the sulfone moiety was found to dramatically improve the thermo-oxidative stability of the neat polyol. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…This char interfered with the mass transfer through the surface of degrading material and thus, at the beginning of degradation, in air a slower mass loss rate was observed than in nitrogen. THIO-ISOH (Figure S8 in supplementary information) showed the same thermal stability both in air and nitrogen up to 500 °C while, at higher temperature, a lower weight was retained in air probably owing to the oxidation of C–S bonding with formation of SO 2 and some sulfate derivatives [ 28,43 ]. When comparing the two diols 4a and 4b , it can be observed that the diol THIO-ISOH retained higher weight than BPA-ISOH at temperature higher than 400 °C in nitrogen and 450 °C in air; also the char residue at high temperature (600 °C) was higher for THIO-ISOH than BPA-ISOH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This char interfered with the mass transfer through the surface of degrading material and thus, at the beginning of degradation, in air a slower mass loss rate was observed than in nitrogen. THIO-ISOH (Figure S8 in supplementary information) showed the same thermal stability both in air and nitrogen up to 500 °C while, at higher temperature, a lower weight was retained in air probably owing to the oxidation of C–S bonding with formation of SO 2 and some sulfate derivatives [ 28,43 ]. When comparing the two diols 4a and 4b , it can be observed that the diol THIO-ISOH retained higher weight than BPA-ISOH at temperature higher than 400 °C in nitrogen and 450 °C in air; also the char residue at high temperature (600 °C) was higher for THIO-ISOH than BPA-ISOH.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the two diols 4a and 4b , it can be observed that the diol THIO-ISOH retained higher weight than BPA-ISOH at temperature higher than 400 °C in nitrogen and 450 °C in air; also the char residue at high temperature (600 °C) was higher for THIO-ISOH than BPA-ISOH. This could be ascribed to a greater promotion of char formation by the sulphur in THIO-ISOH, which hindered the formation of volatile degradation products [ 28 ]; in air sulphur could also provide an additional protection at high temperature in the form of sulfate [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To combine multiple flame retardant elements to one molecule, a polymeric flame retardant containing various flame retardant elements displays obvious advantages, because of its flexible structure and component . Flame retardant elements of phosphorus, nitrogen, and fluorine can be easily and simultaneously incorporated into one polymer chain . The compatibility of the polymeric flame retardant in the polymer matrix is readily adjusted by designing the composition of the polymer .…”
Section: Introductionmentioning
confidence: 99%